METHOD FOR MODEL DEVELOPMENT OF POWER CONSUMPTION MODES AT OIL PIPELINE PART - V. A. Anischenko; N. V. Tokochakova; A. S. Fikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
The paper proposes a method for model development of power consumption modes at oil pipeline part that makes it possible to reduce uncertainty in behaviour of electric power consumption due to application of a sliding average. In order to estimate economy in electric power as a result of power saving measures in the technological process of oil transportation an expediency is proved to select an averaging period which is equal to 30 days.